PEMBELAJARAN BERBASIS E-LEARNING SEBAGAI BENTUK INTEGRASI TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM KURIKULUM BAHASA DAN SASTRA INDONESIA - Tri Nugraha, Setya (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2016)
E-learning is a teaching and learning with computers and technology associated with computers, particularly through the use of the internet that can facilitate the process of interaction of learners with the other learners, learners with sources and digital media, learners with teachers, and learners with a community that is not limited by space and time. Utilization of information and communication technology (ICT) into the e-learning based learning become a priority in the development of the education system to conform to the demands of globalization. Integration technology is defined as the use of various forms of ICT, including the sources of information on the website, multimedia programs, learning objects, and other technological devices, to improve learning. Utilization of ICT in e-learning system also increases the autonomy of learners in learning activities. A dynamic perspective on learners’ autonomy of learning implies their self-awareness to balance their individual experiences in a social context which is facilitated instructionally and experimentally. Access to the online multimedia based learning environment allows learners to choose a variety of appropriate equipment and learning to the objectives and their personal choice and enabling them to adjust or balance their individual and social dimensions of learning. The Internet also provides access to the authentic text, video, and audio that can be adapted to the learning of language and literature.